Mobile development with C# - Shackles, Greg (O'reilly Media, Inc., 2012)
This book shows you how to reuse one codebase across all three platforms by combining the business logic layer of your C# app with separate, fully native UIs. It's an ideal marriage of platform-specific development and the "write once, run everywhere" philosophy. By building a series of simple applications, you'll experience the advantages of using .NET in mobile development and learn how to write complete apps that access the unique features of today's three most important mobile platforms.